Training model of indoor hockey passing techniques For beginners - Firman Rifki; Achmad Sofyan Hanif; Fahmy Fachrezzy (Gladi : Jurnal Ilmu Keolahragaan, 2022)
This study aims to create and implement a indoor hockey passing exercise model for beginners and to measure the effectiveness of the model made. The research will be applied to research subjects as many as 60 students who have the characteristics of novice players, male high school students, aged between 15-17 years who have never participated in indoor hockey training. This study uses a research and development model from Robert Maribe Branch, namely the ADDIE model (Analysis, design, development, implementation, and evaluation). The instrument used is a indoor hockey passing instrument created and developed by researchers. Based on the results of the study, the results of the pre-test were 21.12 and the post-test was 38.7.Significant difference test with SPSS obtained t-count = 71.418 df = 59 and p-value = -0.00 > 0.05 which means there is a significant difference to the results of indoor hockey passing exercises for beginners. Based on the results of statistical testing, it can be concluded that the model of indoor hockey passing technique training for novice players that was developed can effectively improve the indoor hockey passing technique for novice players.